Second primary malignancies in chronic lymphocytic leukaemia: Skin, solid organ, haematological and Richter's syndrome. Issue 1 (13th December 2021) - Shen, Yandong; Coyle, Luke; Kerridge, Ian; Stevenson, William; Arthur, Christopher; McKinlay, Naomi; Fay, Keith; Ward, Christopher; Greenwood, Matthew; Best, Oliver Giles; Solterbeck, Ann; Guminski, Alexander; et al.
Abstract: Chronic lymphocytic leukaemia (CLL) is invariably accompanied by some degree of immune failure, and CLL patients have a high rate of second primary malignancy (SPM) compared to the general population. We comprehensively documented the incidence of all forms of SPM including skin cancer (SC), solid organ malignancy (SOM), second haematological malignancy (SHM) and separately Richter's syndrome (RS) across all therapy eras. Among the 517 CLL/small lymphocytic lymphoma (SLL) patients, the overall incidence of SPMs with competing risks was SC 31.07%, SOM 25.99%, SHM 5.19% and RS 7.55%. Of the 216 treated patients, 106 (49.1%) had at least one form of SPM, and 63 of 106 (29.2% of treated patients) developed an SPM 1.5 years (median) after treatment for their CLL. Melanoma accounted for 30.3% of SC. Squamous cell carcinoma (SCC), including eight metastatic SCCs, was 1.8 times more than basal cell carcinoma (BCC), a reversal of the typical BCC:SCC ratio. The most common SOMs were prostate (6.4%) and breast (4.5%). SHM included seven acute myeloid leukaemia (AML) and five myelodysplasia (MDS) of which eight (four AML, four MDS) were therapy‐related. Any SPM occurred in 32.1% of 53 Monoclonal B‐lymphocytosis (MBL) patients. Age‐adjusted standardised rates of SPM (per 100, 000) for CLL, MBL and the general Australian population were 2648, 1855 and 486.9, respectively. SPMs are a major health burden with 44.9% of CLL patients with having at least one SPM, and apart from SC, associated with significantly reduced overall survival. Dramatic improvements in CLL treatment and survival have occurred with immunochemotherapy and targeted therapies, but mitigating SPM burden will be important to sustain further progress.